HISTORITAS REFORMULASI FILSAFAT HUKUM ISLAM DARI MASA KLASIK HINGGA KONTEMPORER - Burhanudin Ubaidillah, M.; Maria Ulfa, Ana (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
The term Philosophy of Islamic Law is used by Islamic jurists very carefully because the word philosophy is not found in Islamic law sources, but the equivalent meaning according to experts is wisdom. Epistemicly, some expressions show more to an encouragement for the importance of loving wisdom or knowledge. The philosophy of Islamic law as a methodology of thought in subsequent developments is identified with Usul al-fiqh as a methodology for determining Islamic law which contains philosophical elements with rational reasoning. This article focuses on the historical study of the reformulation of Islamic Law Philosophy between Divine Law and Man-Made Law from the classical period (pre-codification) and post-codification of Islamic Law Philosophy. The purpose of this article is to describe the phases of the reconstruction & reformulation of the pre-codification and post-codification of Islamic Legal Philosophy. Efforts to reconstruct & reformulate the Philosophy of Islamic Law prove the richness of the spirit of Islam in building universal benefit and emphasize that the Philosophy of Islamic Law is the result of human reasoning that reflects the plurality of thoughts.